MENCETAK LULUSAN YANG BERKARAKTER DAN BERKUALITAS - PUTU SUBAWA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Establishing a characteristic learners is not an easy and quick effort. It requires con- stant effort and deep reflection to create a barrage of Moral Choice (moral decisions) to be followed up by concrete action, so that it becomes practical and reflective. It takes a certain amount of time to make it all custom and shape one's character or character. The character of the educator can be seen from what is discussed and how he interpreted something that can be seen from what he was talking about. Progressive educators believe in the educational potential for change and make it for knowledge not just to run a money-making job. Each component that determines the quality of education in Indonesia should be equally addressed, ranging from vision-mission to be achieved, educational curriculum, educational facilities and infrastructure, to the keadan learners themselves. These five factors are important components that must be of good concern.